The Effect of Exchange Rates and Interest Rates on Sharia Stock Index in Indonesia: Before and During the Covid-19 Pandemic - Dewi, Sri Yanita; Maesya’bani; Mutmainah, Lu'liyatul (Yayasan Mitra Peduli Indonesia, 2022)
The Islamic Stock Market is starting to take on a role in Indonesia's developing Islamic finance sector. One of the stock price indicators can be seen from the combined sharia stock index, which currently has four types of stock indexes. Previous research found several factors that influence the fluctuations in the sharia stock index, both from internal company factors and macroeconomic conditions. However, little research still compares the effects of exchange rates before and during the Covid-19 pandemic. This study aims to provide new empirical data on the conditions of the Islamic stock market in Indonesia before and during the Covid-19 pandemic. Practically, this research analyses the Islamic capital market and regulators in formulating financial policies. What used the linear regression method to process secondary data in daily data on the JII stock index, JII 70, exchange rates, and interest rates. The study results show that exchange rates and interest rates affect ISSI, JII, and JII70 before and during the pandemic.